2012
DOI: 10.4028/www.scientific.net/amr.518-523.384
|View full text |Cite
|
Sign up to set email alerts
|

Implication of Temporal Dynamics of Microbial Abundance and Nutrients to Soil Fertility under Biochar Application – Field Experiments Conducted in a Brown Soil Cultivated with Soybean, North China

Abstract: A short-term experiment was conducted to investigate responses of microbial community composition and nutrients dynamics to biochar-amended brown soil. We examined the effect of biochar on microbial abundance by plate counting method and microbial community composition changes by DGGE, as well as effect on total and available nutrients N, P and K content. Soil pH measurement was also incorporated into our study. The overall results showed that bacterial abundance increased more than actinomycetes, but … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 35 publications
0
4
0
1
Order By: Relevance
“…Also, soil types had less effect to morphological trait manifestation in soybean compared to maize. Sun et al [2012] suggested that biochar incorporation to brown soil might bring potential benefit to soybean production from N retention in soil and enhanced microbial turnover that resulted with P and K feedback. Our results correspond with Yin et al [2012] study on acid black soil where soybean yield increased by 35.97% compared with the control.…”
Section: Results and Disscusionmentioning
confidence: 99%
“…Also, soil types had less effect to morphological trait manifestation in soybean compared to maize. Sun et al [2012] suggested that biochar incorporation to brown soil might bring potential benefit to soybean production from N retention in soil and enhanced microbial turnover that resulted with P and K feedback. Our results correspond with Yin et al [2012] study on acid black soil where soybean yield increased by 35.97% compared with the control.…”
Section: Results and Disscusionmentioning
confidence: 99%
“…However, biochar aging yields low pH, which promotes the establishment and growth of fungi within the pores of biochar (Zimmermann et al, ). Sun et al () reported that the bacterial communities were more active and dynamic in biochar‐treated brown soils than the fungal communities under natural field conditions, and Gomez, Denef, Stewart, Zheng, and Cotrufo () observed much lower fungi:bacteria (F:B) ratios in four soils (two sandy‐loam, a clay, and a clay‐loam) treated with fast pyrolyzed biochar after 12 months of incubation. It is worth mentioning that F:B of the biochar amended is regulated by the C:N ratio resulting from biochar application (Farrell et al, ) or the natural C:N ratio of the soil (Rousk, Dempster, & Jones, ).…”
Section: Biochar As Soil Amelioratormentioning
confidence: 99%
“…Soil types had less effect on morphological trait manifestation in soybeans. Sun et al [41] suggested that biochar incorporation to brown soil can benefit soybean production by N retention in the soil and enhanced microbial turnover that resulted in P and K feedback. Results obtained by Seremesic et al [40] correspond with a study of Yin et al [42] on acid black soil, in which soybean yield increased by 35.97% compared to the control.…”
Section: Discussionmentioning
confidence: 99%